Pengaruh Struktur Kepemilikan terhadap Kualitas Laba (Studi Empiris Perusahaan Manufaktur yang Listed di BEI Tahun 2009-2011) - Kiki Afialim Fitri; Dwi Fitri Puspa; Yeasy Darmayanti; Siti Rahmi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2019)
This study aims to obtain evidence of the influence of ownership structure as measured by managerial and institutional ownership on earnings quality. This study used 37 companies listed on the Indonesia Stock Exchange. The sample selection was carried out using purposive sampling method. The research period was conducted from 2009 - 2011. To simplify the data processing stage, two categories of variables were used. The first is the independent variable, namely managerial ownership and institutional ownership. Second is the dependent variable is the quality of earnings. The analytical method used is quantitative using multiple regression models. Based on the results of hypothesis testing, it can be concluded that managerial ownership structure and institutional ownership do not have a significant effect on the earnings quality of manufacturing companies listed on the Indonesia Stock Exchange. So it can be concluded that during the observation period in this study the ownership structure as measured by managerial ownership and institutional ownership is not a variable that affects the quality of earnings in manufacturing companies listed on the Indonesia Stock Exchange.